The Contemporary Presidency: How Presidents Utilize Their Emergency Powers. Issue 3 (29th July 2019) - Ouyang, Yu; Morgan, Michael A.
Abstract : What explains how presidents utilize their emergency powers? In the recent political battle with Congress over the U.S.–Mexico border, President Donald Trump announced his willingness to invoke his emergency powers to construct the controversial wall if Congress continued to oppose his decisions. While his action was met with strong, mostly partisan responses, the declaration of national emergencies to fulfill policy objectives is not unique to the Trump administration. Building on the unilateral presidency literature, we report the results of a pilot project on how the political environment impacts the use of national emergencies in U.S. foreign policy. Results add to our understanding of a current political debate and to a broader comprehension of presidential emergency powers.